2017
DOI: 10.11648/j.ajns.20170603.23
|View full text |Cite
|
Sign up to set email alerts
|

Staff Nurses Perception Toward Organizational Culture and Its Relation to Innovative Work Behavior at Critical Care Units

Abstract: Abstract:Background: Health care organization culture can influenced by its ability to manage human resources and has a strong impact on its performance. Aim: the study aimed to assess staff nurses perception toward organizational culture and its relation to their innovative work behavior at critical care units. Setting: The study was conducted in critical care units at Benha University Hospital. Research design: descriptive correlation design was utilized to conduct this study. Sample: Convenience sample cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
2
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 10 publications
2
11
2
2
Order By: Relevance
“…The current study findings go in the same line with that of a study conducted by (18) , who examined the relationship between leadership behaviors, organizational climate, and innovative work behaviors among nurses, in Egypt, and revealed that slightly less than half of them have a high average level of innovative work behaviors. Conversely, the previous result goes in disagreement with that of a study conducted by Kamel& Aref (26) , who investigated the perception of staff nurses about organizational culture and its relationship to innovative work behaviors at critical care units, in Egypt, and pointed out that half of staff nurses had a highly level of innovative work behaviors. Additionally, Abd El-Fattah (27) , who conducted a study about innovation behaviors levels and its relation with TIGER-based nursing informatics competencies among critical care nurses, in Egypt, confirmed that more than half of participants had a moderate level of innovative work behaviors.…”
Section: Discussioncontrasting
confidence: 70%
“…The current study findings go in the same line with that of a study conducted by (18) , who examined the relationship between leadership behaviors, organizational climate, and innovative work behaviors among nurses, in Egypt, and revealed that slightly less than half of them have a high average level of innovative work behaviors. Conversely, the previous result goes in disagreement with that of a study conducted by Kamel& Aref (26) , who investigated the perception of staff nurses about organizational culture and its relationship to innovative work behaviors at critical care units, in Egypt, and pointed out that half of staff nurses had a highly level of innovative work behaviors. Additionally, Abd El-Fattah (27) , who conducted a study about innovation behaviors levels and its relation with TIGER-based nursing informatics competencies among critical care nurses, in Egypt, confirmed that more than half of participants had a moderate level of innovative work behaviors.…”
Section: Discussioncontrasting
confidence: 70%
“…Nursing managers who are aware of the relationship between organizational culture and empowerment among nurses can encourage them to be empowered with the use of their talents, knowledge, skills and experiences (Kamel & Aref, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Bir başka çalışmada da, hemşirelerin çalıştığı klinik ve medeni durumu ile bireysel yenilikçilik düzeyleri arasında anlamlı fark olmadığı; Y kuşağı, çocuk sahibi olmayan ve bilimsel toplantılara katılan hemşirelerin ise bireysel yenilikçilik düzeylerinin anlamlı seviyede daha yüksek olduğu bulunmuştur (22) . Yoğun bakım ünitelerinde çalışan hemşirelerin örgütsel kültür algıları ve yenilikçi iş davranışları ile ilişkisinin değerlendirildiği bir çalışmada ise, hemşirelerin çoğunun örgütsel kültürle ilgili olumlu algıya sahip olduğu ve yenilikçi iş davranışları ile örgütsel kültür algıları arasında anlamlı bir ilişki olduğu bulunmuştur (15) .…”
Section: Discussionunclassified
“…Tanıtıcı Bilgi Formu: Yoğun bakım hemşirelerinin sosyodemografik verileri ile yenilik-yenilikçi uygulamalara ilişkin özelliklerini içeren literatürden yararlanılarak araştırmacılar tarafından hazırlanan açık ve kapalı uçlu sorulardan oluşan toplam 19 soruyu içermektedir (5,(13)(14)(15) . (13) .…”
Section: Veri Toplama Araçlarıunclassified